2008
DOI: 10.1186/1471-2148-8-36
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and evolution of the inverted repeat-large single copy junctions in the chloroplast genomes of monocots

Abstract: BackgroundVarious expansions or contractions of inverted repeats (IRs) in chloroplast genomes led to fluxes in the IR-LSC (large single copy) junctions. Previous studies revealed that some monocot IRs contain a trnH-rps19 gene cluster, and it has been speculated that this may be an evidence of a duplication event prior to the divergence of monocot lineages. Therefore, we compared the organizations of genes flanking two IR-LSC junctions in 123 angiosperm representatives to uncover the evolutionary dynamics of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
363
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(388 citation statements)
references
References 75 publications
23
363
2
Order By: Relevance
“…Wang et al (2008) also demonstrated a further expansion of the IR at the 39 LSC boundary to include rps19 in plastid genomes of Asparagales and commelinid (Commelinales, Zingiberales, Arecales, Dasypogonaceae, and Poales) species included in their study. They concluded that plastid genomes of the more derived monocots, including Asparagales, and members of the commelinid clade, are all likely to share an expansion of the IR to include rps19.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Wang et al (2008) also demonstrated a further expansion of the IR at the 39 LSC boundary to include rps19 in plastid genomes of Asparagales and commelinid (Commelinales, Zingiberales, Arecales, Dasypogonaceae, and Poales) species included in their study. They concluded that plastid genomes of the more derived monocots, including Asparagales, and members of the commelinid clade, are all likely to share an expansion of the IR to include rps19.…”
Section: Discussionmentioning
confidence: 84%
“…They further concluded that the endpoint of the IR is highly conserved because across Asparagales and commelinids only 35-99 bp were duplicated beyond rps19. The Wang et al (2008) study is based on results of Sanger sequencing at the IR-LSC boundaries to identify genes present and reverse transcriptase-polymerase chain reaction (RT-PCR) assays to verify transcription of the trnH-GUG and/or rps19 genes. The results of this study are not entirely concordant with the Wang et al study with respect to the duplication of rps19.…”
Section: Discussionmentioning
confidence: 99%
“…However, the contraction and expansion at the borders of IR regions are common evolutionary events, and are major causes of rearrangements and size variation [7,15,38]. In this study, we compared the SC/IR boundaries among six Fritillaria genomes.…”
Section: Discussionmentioning
confidence: 99%
“…The SSC region of F. ussuriensis was 423 bp shorter than that of F. cirrhosa. IR contraction and expansion are common evolutionary events and contribute to genome size variation [6,7,24]. We analyzed the border structure of the two cp genomes.…”
Section: Comparison Of Chloroplast Genomes With Those Of Other Fritilmentioning
confidence: 99%
“…Chloroplast is a plant organelle containing its own circular DNA molecules that vary in size from 120 kb to 160 kb depending on the plant species. Chloroplast DNA (CpDNA) is largely composed of LSC, SSC, and they encode 4 rRNAs, 30 tRNAs, and 80 proteins on average, which are involved in photosynthesis or the expression of chromosomal genes (Palmer 1985;Jansen et al 2005;Wang et al 2008).…”
Section: Introductionmentioning
confidence: 99%